2011
DOI: 10.1016/j.jtcvs.2010.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurround, nonuniform, biventricular-capable direct cardiac compression provides Frank-Starling recruitment independent of left ventricular septal damage

Abstract: The HeartPatch DCC support of LV and RV function results from improvement of the systolic septal-lateral fractional change that is not influenced by septal infarction. The latter attenuated LV to RV device energy delivery during LV patch actuation but enhanced RV energy delivery during RV patch actuation. This DCC technique can provide effective support in high-risk RV failure situations arising from left ventricular assist device use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…First, direct effects on the myocardial region where pressure is applied, and second, a circumferential effect caused by the 3D changes during inflation of two or three support units. This observation is supported by Mau et al, 7 who reported that cavity volume reduction was achieved because the septal-lateral short-axis change exceeded the anterior-posterior lengthening.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…First, direct effects on the myocardial region where pressure is applied, and second, a circumferential effect caused by the 3D changes during inflation of two or three support units. This observation is supported by Mau et al, 7 who reported that cavity volume reduction was achieved because the septal-lateral short-axis change exceeded the anterior-posterior lengthening.…”
Section: Discussionsupporting
confidence: 61%
“…This is an important observation as Mau et al stated that "heart surrounding configuration … is likely to constrain ventricular filling and impair early diastolic relaxation." 7 In fact, our results showed a trend toward a decrease in time constants of the PV loops dp/dt min and τ during mechanical support (see Figure, Supplemental Digital Content, http:// links.lww.com/ASAIO/A186). Customization also enabled correct positioning of the implants in a minimally invasive procedure on the beating heart, ensuring correct positioning of the pneumatic units in their predefined locations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This design allowed the two patch chambers to be controlled independently so that compression intensity and frequency could be customized for each ventricle. [28,50] An ECG was used to synchronize the movement of the device with the heart. Potential limitations of the HeartPatch include delamination of the patches from the cardiac surface and the rupture of the heart muscle.…”
Section: Direct Cardiac Compression Devicesmentioning
confidence: 99%